Childhood Obesity: A Public Health Crisis - Salama, Ali (National Journal of Community Medicine, 2023)
Over the past three decades, pediatric obesity prevalence has significantly increased globally. This obesity epidemic is thought to be the cause of the rising incidence of illnesses like type 2 diabetes in youngsters. Understanding the genetics and physiology of hunger control has advanced greatly, and as a result, the reasons for various unusual obesity diseases have been clarified. Children of thin parents may do better in weight control than children of obese parents. Adherence to exercise is likely to be a problem with obese children, and the choice or design of an exercise program should take these adherence problems into account. The nutritional adequacy of the child's diet should be evaluated both in terms of what the child is eating as well as in terms of the prescribed diet. We have learned almost little about how to prevent or reverse childhood obesity from these rare illnesses, though. Due to the modern sedentary lives of children, calorie intake and activity recommendations require re-evaluation and enhanced quantification at the population level. Given the growing understanding of the so-called energy gap, the current calorie recommendations for individual treatment may be too conservative. High-quality multicentre studies with long-term follow-ups are required despite improvements in the quality of research into prevention and therapy. During this time, efforts should be made to reduce intake and enhance energy expenditure through preventative and therapeutic measures. Increased efforts should be undertaken on all fronts to maintain this potentially promising trend in light of recent data that suggest that the spiralling rise in pediatric obesity prevalence may be slowing.